The restricted detour polynomials of a prism and some wheel related graphs. Issue 4 (19th May 2021) - Abdullah, Herish Omer; Ali, Ivan Dler
Abstract: The restricted detour index of a connected graph G is equal to the sum of restricted detour distances of all unordered pairs of vertices of G . The restricted detour polynomial of graph G is defined as, where C *( G, k ) is the number of unordered pairs of vertices of G laying at restricted detour distance k from each other and δ * is restricted detour diameter of G . In this paper, restricted detour polynomials and restricted detour indices of prism graphs, helm graphs and closed helm graphs have been computed.